2018
DOI: 10.2993/0278-0771-38.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Generating Pastoral Skills through Work and Play in the Daily Life of Maasai Children in Kenya

Abstract: Pastoralists in East Africa are well known for their abilities in effective livestock and natural resource management in the dynamic arid and semi-arid ecosystem in which they live. Their ethnobiological knowledge, manifest in their skills of managing livestock and natural resources, is generated from the daily experiences of individuals in different landscapes. Since the early twentieth century, the pastoralist Maasai have gradually experienced land fragmentation and lifestyle changes. However, how Maasai chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…Empirical research also suggests that the prevalence of vertical transmission can be overestimated in self-reports about the learning model [ 57 ]. Moreover, because children learn a lot from other children, this indicates the importance of horizontal transmission in the formation of knowledge and child practice [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Empirical research also suggests that the prevalence of vertical transmission can be overestimated in self-reports about the learning model [ 57 ]. Moreover, because children learn a lot from other children, this indicates the importance of horizontal transmission in the formation of knowledge and child practice [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by the literature (Barreau et al 2016; Iniesta-Arandia et al 2015; Mathez-Stiefel and Vandebroek 2012) and our results, immersion in the local environment and lived experiences with incidental traditional medicine is a factor in the transmission of knowledge. For many Maasai communities, learning traditional medicine was incorporated into daily life as chores (Tian 2018). Herders learned about herbs while out with cattle (Bruyere 2016; Trimarco 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Now we go to the clinic or the hospital because we are in town. (39-year-old participant, 2018) Most of them use these herbs, or maybe if their parents are here in town then communities, learning traditional medicine was incorporated into daily life as chores (Tian 2018). Herders learned about herbs while out with cattle (Bruyere 2016;Trimarco 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In a Tanzanian case study including 57 households (mothers/female guardians) and 114 children, both mothers and children reported that more girls (aged 10-17) than boys of the same age engaged in collecting wood and fetching water, and that they spent more average hours than boys doing these necessary household tasks and that these hours often took place during the week (DeGraff et al, 2017). Gendered chore assignments are often culturally driven, as such social norms are perpetuated through the tradition of modeling and emulation in play and daily work; as one anthropologist noted, Maasai community members in southern Kenya would laugh if a boy carried firewood back home (Tian, 2019). There is also an economic aspect to such practices.…”
Section: Chores and Gender In Sub-saharan Africamentioning
confidence: 99%